Aqueous phase adsorption of organic/inorganic contaminants by eucalyptus bark (eucalyptus sheathiana) biomass - Afroze, Sharmeen (Curtin University, 2016)
This research demonstrates the adsorption characteristics of raw and chemically treated eucalyptus bark (Eucalyptus sheathiana) biomass as a cost effective agricultural solid waste adsorbent in the removal of organic/inorganic contaminants from their aqueous phase. Mechanism of adsorption and identification of various process parameters and their optimum values have been explored here. The research outcomes are to show large potential of eucalyptus bark to treat dye and metal bearing wastewaters alternative to many costly commercial adsorbents.